The Routledge companion to public humanities scholarship
1 online resource (xxi, 434 pages)
Keywords: "Across humanities disciplines, public scholarship brings academics and community members and organizations together in mutually-beneficial partnership for research, teaching, and programming. While the field of publicly engaged humanities scholarship has been growing for some time, there are few volumes that have attempted to define and represent its scope. The Routledge Companion to Public Humanities Scholarship brings together wide-ranging case studies sharing perspectives on this work, grounded in its practice in the United States"--